Coliforms in the water and hemoglobin concentration are predictors of gastrointestinal morbidity of Bangladeshi children ages 1-10 years - Bhargava, Alok; Bouis, Howarth E.; Hallman, Kelly; Hoque, Bilquis A.. (Wiley, 2003)
The presence of pathogens in the water and children's poor nutritional status are likely to increase morbidity in developing countries. Understanding the interactions between the environmental and nutritional factors is important from the standpoint of improving child health. In this study, we analyzed the effects of fecal and total coliforms in the water available at the source and that stored in the household on the spells of gastrointestinal morbidity of 99 Bangladeshi children at three time points in an 8‐month period. Fecal and total coliforms in the stored water were significant predictors (P < 0.05) of morbidity that was modeled using dynamic random effects models. Moreover, children with better hemoglobin status experienced lower morbidity. An empirical model for the proximate determinants of hemoglobin concentration showed significant negative associations between children's hookworm loads and hemoglobin. While the children's intakes of bioavailable iron, iron from meat, fish, and poultry, and iron from animal sources were not significant predictors of hemoglobin status in this population, the need for broader interventions for improving child health was apparent. Am. J. Hum. Biol. 15:209–219, 2003. © 2003 Wiley‐Liss, Inc.